PERAN ALIM ULAMA, TUO TENGGANAI SERTA CERDIK PANDAI DALAM MEMBANGUN CITRA PENDIDIKAN ISLAM DAN PERADABAN MELAYU JAMBI DI TANAH PILIH PUSAKO BATUAH KOTA JAMBI - Al Bima; Ahmad Ridwan; Sumirah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
His study aims to analyze the roles of alim ulama, tuo tengganai, and cerdik pandai in building the image of Islamic education and Malay Jambi civilization in Tanah Pilih Pusako Betuah, Jambi City. Islamic education within the Malay Jambi community is not merely understood as the transmission of ritual religious knowledge, but also as a process of moral formation, reinforcement of customary values, and the development of a social order based on the philosophy adat basendi syara’, syara’ basendi Kitabullah (custom is founded upon Islamic law, and Islamic law is founded upon the Qur’an). This research employed a qualitative approach with a field research design. Data were collected through in-depth interviews, observation, and documentation involving alim ulama, tuo tengganai, cerdik pandai, and administrators of the Malay Customary Institution (Lembaga Adat Melayu/LAM) of Jambi City. The data were analyzed using descriptive qualitative techniques through data reduction, data display, and conclusion drawing. The findings indicate that alim ulama play a central role in moral development, religious guidance, exemplary leadership, and the resolution of socio-religious issues within the community. Tuo tengganai contribute to preserving and transmitting Malay customary values that are aligned with Islamic teachings, while also serving as a bridge between tradition and social life. Meanwhile, cerdik pandai play an important role in strengthening intellectual discourse, developing Islamic education, and transforming values through educational and scholarly approaches. The synergy among these three actors forms a holistic and contextual image of Islamic education rooted in local wisdom. The study also reveals that supporting factors include the strong religious culture of the community, public trust in religious and customary leaders, and the existence of active religious and customary institutions. Conversely, inhibiting factors consist of the influence of modernization, the narrowing interpretation of Islamic education as merely ritual practice, and weak regeneration of religious and customary leaders. Therefore, it can be concluded that alim ulama, tuo tengganai, and cerdik pandai constitute the main pillars in sustaining Islamic education and Malay Jambi civilization in Jambi City.